Ethical Dilemmas in the Classroom: A Narrative Approach to Professional Ethics in Indian Teacher Education - Aditi Verma; Karan Singh; Meera Gupta (International Journal of Educational Narratives, 2025)
Background. Professional ethics is a critical yet often underexplored dimension in teacher education, particularly in contexts where cultural, institutional, and systemic challenges intersect. In India, where educators regularly face value conflicts in classrooms ranging from caste discrimination to gender norms and curriculum constraints there is a growing need to address how ethical dilemmas are experienced and navigated by pre-service teachers. Purpose. This study explores ethical decision-making in teacher education through a narrative inquiry approach, focusing on the lived experiences of student-teachers across four Indian teacher training institutes. Method. A total of 28 participants engaged in reflective journaling and semi-structured interviews, recounting ethical tensions encountered during practicum or coursework. Thematic narrative analysis revealed recurring dilemmas related to authority, bias, institutional silence, and cultural contradiction. Results. Participants often expressed uncertainty, emotional distress, and conflict between personal values and institutional expectations. However, the process of narrating these experiences also served as a reflective tool, enabling critical ethical reasoning and professional growth. Conclusion. The study concludes that narrative reflection can be a transformative pedagogical strategy in teacher education, fostering ethical sensitivity and professional identity development in complex educational environments.